Irrumpir en la continuidad: desafíos espacio-temporales en las prácticas culturales de una pequeña ciudad bonaerense - Re, Valeria (2024)
This article proposes a theoretical key to explore temporalities in the cultural processes of a non-metropolitan city. From a qualitative and ethnographic approach, it examines the spatial and temporal markers expressed in the cultural and artistic practices of a small-scale city in the northwest of Buenos Aires Province during the period 2019-2023. The findings reveal interconnections among space, time, and culture, organized around the cultural production of personal and institutional trajectories, which explain the principles of continuity, stability, and stillness typically associated with such territories.